Confronting an Upsurge in Opiate Deaths with Limited Resources - Andrew, Thomas A. (Acad Forensic Pathol, 2017)
The dramatic increase in drug-related deaths in the last decade has presented fiduciary and logistical difficulties to medicolegal jurisdictions of all types and sizes. New Hampshire, with a centralized state medical examiner system of death investigation, has been confronted with the task of investigating these drug-related deaths against the backdrop of statutory hurdles inhibiting a nimble response to the situation. This has led to a collaborative approach with law enforcement and the state Department of Justice in terms of triaging drug deaths to full autopsy versus external examination with toxicology testing. Preliminary data suggest that between 11 and 13% of suspected drug deaths have an alternative cause of death revealed by autopsy. Positive toxicological findings were documented in 97.5% of cases in which only an external examination was performed; however, some of these cases may have had undetected, significant internal findings that could have accounted for an alternative cause of death if an autopsy had been performed. While the case triage system described has temporarily addressed the acute problem, the issue of the medical examiner's appropriate role in the adequate evaluation of public health and safety remains extant. Furthermore, noncompliance with the National Association of Medical Examiners inspection and accreditation standards puts this agency, and others facing the same issues, at risk of losing full accreditation status until such resource issues are addressed by legislators and other stakeholders in the quality of medicolegal death investigation in the United States.